Hydrophobic kenaf nanocrystalline cellulose for the binding of curcumin. (1st May 2017) - Zainuddin, Norhidayu; Ahmad, Ishak; Kargarzadeh, Hanieh; Ramli, Suria
Highlights: CTAB modified NCC was investigated for the binding of curcumin. Significant amount of curcumin was bound on the CTAB modified NCC. The binding efficiency of curcumin was dependent on the concentration of CTAB. As the concentration of CTAB increased, the binding efficiency was decreased. Abstract: Nanocrystalline cellulose (NCC) extracted from lignocellulosic materials has been actively investigated as a drug delivery excipients due to its large surface area, high aspect ratio, and biodegradability. In this study, the hydrophobically modified NCC was used as a drug delivery excipient of hydrophobic drug curcumin. The modification of NCC with a cationic surfactant, cetyl trimethylammonium bromide (CTAB) was used to modulate the loading of hydrophobic drugs that would not normally bind to NCC. The FTIR, Elemental analysis, XRD, TGA, and TEM were used to confirm the modification of NCC with CTAB. The effect of concentration of CTAB on the binding efficiency of hydrophobic drug curcumin was investigated. The amounts of curcumin bound onto the CTAB–NCC nanoparticles were analyzed by UV–vis Spectrophotometric. The result showed that the modified CTAB–NCC bound a significant amount of curcumin, in a range from 80% to 96% curcumin added. Nevertheless, at higher concentration of CTAB resulted in lower binding efficiency.